Mechanisms of glucocorticoid resistance in hypereosinophilic syndromes. Issue 12 (27th October 2019) - Stokes, Kindra; Yoon, Pryscilla; Makiya, Michelle; Gebreegziabher, Meheret; Holland‐Thomas, Nicole; Ware, JeanAnne; Wetzler, Lauren; Khoury, Paneez; Klion, Amy D.
Abstract: Background: Glucocorticoids (GC) are considered first‐line therapy for most patients with hypereosinophilic syndrome (HES). Although response rates are generally high, many patients require moderate to high doses for control of eosinophilia and symptoms, and up to 15% of patients do not respond at all. Despite this, little is known about the mechanisms of GC resistance in patients with HES. Objective: To explore the aetiology of GC resistance in HES. Methods: Clinical data and samples from 26 patients with HES enrolled on a prospective study of GC responsiveness and 23 patients with HES enrolled on a natural history study of eosinophilia for whom response to GC was known were analysed retrospectively. Expression of GC receptor isoforms was assessed by quantitative RT‐PCR in purified eosinophils. Serum cytokine levels were quantified by suspension array assay in multiplex. Results: Despite an impaired eosinophil response to GC after 7 days of treatment, the expected rise in absolute neutrophil count was seen in 7/7 GC‐resistant patients, suggesting that GC resistance in HES is not a global phenomenon. Eosinophil mRNA expression of glucocorticoid receptor (GR) isoforms (α, β, and P) was similar between GC‐sensitive (n = 20) and GC‐resistant (n = 9) patients with HES. Whereas geometric mean serum levels were also comparable between GC‐r (n = 11) and GC‐s (n = 19) for all cytokines tested, serum IL‐5 levels were >100 pg/mL only in GC‐r patients. Conclusions and Clinical Relevance: These data suggest that the mechanism of GC resistance in HES is not due to a global phenomenon affecting all lineages, but may be due, at least in some patients, to impairment of eosinophil apoptosis by increased levels of IL‐5.